Biomarker cystatin B expression correlates with pathogenesis in cervical cancer - Danjuan Ye; Xiaoling Duan; Bin Guan; Jia Yuan; Yan Zhu; Jimin Shi; Qi Lu; Guoxiong Xu (Journal of International Medical Research, 2024)
Objective Cervical cancer (CC) is one of the most common gynecologic malignancies worldwide. Although rapid improvements have been made regarding its prevention and treatment, little is known about disease pathogenesis and the clinical relevance of reliable biomarkers. The present study evaluated the expression of cystatin B (CSTB) as a potential biomarker of CC. Methods Tissue microarray analysis and immunohistochemical staining were performed to detect CSTB expression, while CSTB mRNA and protein expression levels of freshly isolated CC tissue were measured by quantitative real-time PCR and western blot, respectively. Bioinformatics were used to analyze the CSTB co-expression network and functional enrichments. Results We observed high CSTB mRNA and protein expression levels in CC tissues, which was confirmed by tissue microarray in a comparison with paired adjacent non-cancerous cervical tissue samples. CSTB gene enrichments and associations with co-expressed genes were also observed. Further analysis showed that elevated CSTB expression was associated with pathological progress in CC. Conclusion Our data demonstrate that CSTB has the potential to be used as a tissue biomarker with clinical value in patients with CC, which may aid the development of intervention strategies.